Bringing 3D tumor models to the clinic – predictive value for personalized medicine. Issue 2 (18th January 2017) - Halfter, Kathrin; Mayer, Barbara
Abstract: Current decision‐guiding algorithms in cancer drug treatment are based on decades of research and numerous clinical trials. For the majority of patients, this data is successfully applied for a systemic disease management. For a number of patients however, treatment stratification according to clinically based risk criteria will not be sufficient. The most effective treatment options are ideally identified prior to the start of clinical drug therapy. This review will discuss the implementation of three‐dimensional (3D) cell culture models as a preclinical testing paradigm for the efficacy of clinical cancer treatment. Patient tumor‐derived cells in 3D cultures duplicate the individual tumor microenvironment with a minimum of confounding factors. Clinical implementation of such personalized tumor models requires a high quality of methodological and clinical validation comparable to other biomarkers. A non‐systematic literature search demonstrated the small number of prospective studies that have been conducted in this area of research. This may explain the current reluctance of many physicians and insurance providers in implementing this type of assay into the clinical diagnostic routine despite potential benefit for patients. Achieving valid and reproducible results with a high level of evidence is central in improving the acceptance of preclinical 3D tumor models. Abstract : This review discusses the use of three‐dimensional (3D) cell culture models as a preclinical testing system for clinical cancer treatment. A literature search revealed only a small number of conducted studies. This may explain the current reluctance in the use of this technology in the clinical routine despite potential benefit for patients.